2022
DOI: 10.1073/pnas.2205314119
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ORP2A mediates ER–autophagosomal membrane contact sites and regulates PI3P in plant autophagy

Abstract: Autophagy is an intracellular degradation system for cytoplasmic constituents which is mediated by the formation of a double-membrane organelle termed the autophagosome and its subsequent fusion with the lysosome/vacuole. The formation of the autophagosome requires membrane from the endoplasmic reticulum (ER) and is tightly regulated by a series of autophagy-related (ATG) proteins and lipids. However, how the ER contacts autophagosomes and regulates autophagy remain elusive in plants. In this study, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 65 publications
6
28
0
Order By: Relevance
“…Three-dimensional EM has been used to overcome these limitations. Electron tomography previously revealed tight and extensive contacts of phagophores with the ER (Biazik et al, 2015;Hayashi-Nishino et al, 2009;Uemura et al, 2014;Ye et al, 2022;Ylä-Anttila et al, 2009). Contacts with putative ER exit sites and Golgi cisternae and connections to endolysosome-related structures have also been observed (Biazik et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional EM has been used to overcome these limitations. Electron tomography previously revealed tight and extensive contacts of phagophores with the ER (Biazik et al, 2015;Hayashi-Nishino et al, 2009;Uemura et al, 2014;Ye et al, 2022;Ylä-Anttila et al, 2009). Contacts with putative ER exit sites and Golgi cisternae and connections to endolysosome-related structures have also been observed (Biazik et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Because autophagosomes are formed de novo, their formation relies on the import of lipids and other components from other organelles. Previous reports showed that autophagosome formation undergoes in contact with the endoplasmic reticulum (ER) (Axe et al, 2008;Biazik et al, 2015;Bieber et al, 2022;Gudmundsson et al, 2022;Hayashi-Nishino et al, 2009;Uemura et al, 2014;Ye et al, 2022;Ylä-Anttila et al, 2009), ER exit sites (Biazik et al, 2015), mitochondria (Biazik et al, 2015;Bieber et al, 2022;Hailey et al, 2010), ERmitochondria contact sites (Hamasaki et al, 2013), the Golgi apparatus (Biazik et al, 2015;Nishida et al, 2009), lipid droplets (Bieber et al, 2022;Dupont et al, 2014;Ogasawara et al, 2020), endosomes (Biazik et al, 2015), and the nuclear envelope (Bieber et al, 2022;English et al, 2009). These organelles form contacts with phagophores and can communicate with them through vesicular or non-vesicular transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In human and yeast, ORPs often depend on the PH domain to specifically bind certain PIPs to recruit other protein to target specific membrane (Levine & Munro, 1998; Levine & Munro, 2002). Another study in plant also proved a strong association between ORP2A and a set of PIPs (Ye et al ., 2022). Our data further confirmed the connection between ORP2A and PIPs and pinpointed the PH domain function for ORP2A in PIP binding (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…However, studies relating to ORPs in plants are very little. A recent study indicates that ORP2A has a function in autophagy regulation at ER – autophagosomal MCSs (Ye et al ., 2022), which demonstrates its important roles in intracellular processes in plants. In our study, we found that the knockout mutant orp2a-1 and its CRISPR lines exhibit obvious phenotypes in the change of organ shape similar to agb1-2 (such as the rounder leaf, shorter and blunter silique) (Fig.1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation